B=(2x-1)(2x-1)+(2x-1)(3x+5) D= (2x+7)(5x+4)-(2x+7)(x+11)

devellopper et reduire B devellopper et reduire D

factoriserB factoriser D

C=(x-1)(2x+5)-(x+1)(2x+5)

*devellopper et reduire C

factoriser C

A= (x+2)(x-3)+(x-3)

develloper et reduire A

factoriser A.

puis calculer A pour x=3

2

Réponses

2012-10-09T23:45:20+02:00

factoriser

A = (x+2)(x-3)+(x-3) = (x-3) [(x+2)+1] = (x-3)(x+3) = x²-9

B = (2x-1)(2x-1)+(2x-1)(3x+5) = (2x-1)[(2x-1)+(3x+5)]= (2x-1)(5x+4)

C= (x-1)(2x+5)-(x-1)(2x+5) = (2x+5)[(x-1)-(x-1)]=(2x+5)-2 = -2(2x+5)

D = (2x+7)(5x+4)-(2x+7)(x+11) = (2x+7)[(5x+4)-(x+11)]=(2x+7)(4x-7)

 

2012-10-10T00:41:52+02:00

A = (x+2)(x-3)+(x-3)

= (x-3) [(x+2)+1]

= (x-3)(x+3) = x²-9

 

B = (2x-1)(2x-1)+(2x-1)(3x+5)

= (2x-1)[(2x-1)+(3x+5)]

= (2x-1)(5x+4)